Dynamische Preissetzung: Wer profitiert? - Stefan Genth; Michael Schleusener; Peter Kenning; Maximilian Pohst; Johannes Remmel; Bernd Weber; Nadine Gier; Martin Schmidt-Kessel (Wirtschaftsdienst, 2016)
Im September 2016 kamen Verbraucherforscher an der Heinrich-Heine-Universität Düsseldorf zu einem Forum des Netzwerks Verbraucherforschung zusammen. Ziel dieses Forums war es, gemeinsam eine Agenda für die mit dem Dynamic Pricing verbundenen Implikationen für die Verbraucherforschung und die Verbraucherpolitik zu entwickeln. Im Zeitgespräch dokumentieren wir die Vorträge aus der Perspektive des Einzelhandels, der Verbraucherforschung, der Neurowissenschaft, der Rechtswissenschaft sowie der Verbraucherpolitik. – – In the context of digitalisation, recent approaches for automatic price adjustment are gaining importance. However, these approaches can affect consumer behaviour in a way which is disadvantageous for consumers, businesses and the state as a whole. In September 2016, consumer researchers met at the Heinrich Heine University in Düsseldorf in order to discuss the impact of dynamic pricing from the viewpoint of their research fields. As the articles make clear, the researchers found that dynamic pricing based on competitors' prices is common, while personalised prices are extremely rare. The question arises as to what extent consumers consider dynamic prices unfair. The experts disagree about the necessity of a stricter legal regulatory framework. Furthermore, digital technology can be used to help consumers find their way through the complex online world. Ultimately, the question of who profits - the consumer or the trader - has not been settled. The discussants conclude that there is need for further research in many different research fields.
Keywords: 330